Mencius : A New Translation Arranged and Annotated For The General Reader - Dobson, W. A. C. H. (Book collections on Project MUSE., 1963)
The Works of Mencius provides an admirable insight into one of the streams of thought of the Chinese. This new translation, especially arranged and annotated aims at rendering an Archaic Chinese original in a modern and unadorned prose.